WAVELET SOLUTIONS AND STABILITY ANALYSIS OF PARABOLIC EQUATIONS - Mishra, Vinod; -, Sabina (IndoMS, 2010)
In this paper wavelet solutions of extended Sideways and non stan-dard parabolic equations have been analyzed along with stabilization and errorsestimation.DOI :Â http://dx.doi.org/10.22342/jims.16.1.32.69-87